Individual Processing Speed Analysis for Traffic Sign Detection and Recognition - Md Ghazaly, Mariam; Mohd Ali, Nursabilillah; Mohd Sobran, Nur Maisarah; Ab. Shukur, Syahar Azalia; Tuani Ibrahim, Ahmad Fayeez (2013)
The present paper describes the individual Processing Speed Analysis for Traffic Sign Detection and Recognition